2010
DOI: 10.1073/pnas.0914351107
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule screen identifies reactive oxygen species as key regulators of neutrophil chemotaxis

Abstract: Neutrophil chemotaxis plays an essential role in innate immunity, but the underlying cellular mechanism is still not fully characterized. Here, using a small-molecule functional screening, we identified NADPH oxidase–dependent reactive oxygen species as key regulators of neutrophil chemotactic migration. Neutrophils with pharmacologically inhibited oxidase, or isolated from chronic granulomatous disease (CGD) patients and mice, formed more frequent multiple pseudopodia and lost their directionality as they mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
2
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 27 publications
8
103
2
7
Order By: Relevance
“…Interestingly, ROS were recently identified as being important for directionality in a study of small-molecule inhibitors of directional migration. 45 That study also showed that neutrophils from chronic granulomatous disease patients, which lack significant ROS production, also exhibit defects in chemotaxis. In addition, an intriguing finding that neutrophils are able to migrate along H 2 O 2 gradients could be explained by this mechanism.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, ROS were recently identified as being important for directionality in a study of small-molecule inhibitors of directional migration. 45 That study also showed that neutrophils from chronic granulomatous disease patients, which lack significant ROS production, also exhibit defects in chemotaxis. In addition, an intriguing finding that neutrophils are able to migrate along H 2 O 2 gradients could be explained by this mechanism.…”
Section: Discussionmentioning
confidence: 86%
“…In our studies we use a concentration of 5 μM for cell labeling and we are able to successfully track labeled neutrophils in blood, bone marrow and kidneys of Candida-infected recipient mice for at least 4 hr after neutrophil transfer 6 . Besides CellTracker Green and CellTracker Orange, other dyes including CellTracker Violet, CFSE and SNARF-1 have also been used successfully to label mouse bone marrow-derived neutrophils for adoptive transfer experiments 11,19,20 . In addition, the CellTracker Green and CellTracker Orange dyes have been effectively used at a similar concentration of 5 μM for labeling mouse splenic T cells for adoptive transfer and tracking experiments 21 .…”
Section: Discussionmentioning
confidence: 99%
“…29 It is clear that ROS is important for migration; when nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, the enzyme that generates superoxide, is blocked in neutrophils, they experience decreased migration. 30 However, excess levels of ROS are also detrimental as van Aalst et al showed that incubation of endothelial cells with oxidized lowdensity lipoprotein both increased ROS levels and decreased cell migration compared to cells cultured in a normal medium. 31 Prolonged exposure to ROS does not necessarily decrease CXCR4 expression as prior studies have shown that only very high levels of AGEs (500 lg/mL) decreased receptor expression.…”
Section: Discussionmentioning
confidence: 99%